2016
DOI: 10.1007/s11442-016-1296-x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying sources and hazardous risks of heavy metals in topsoils of rapidly urbanizing East China

Abstract: With rapid economic and social development, soil contamination arising from heavy metals has become a serious problem in many parts of China. We collected a total of 445 samples (0-20 cm) at the nodes of a 2 km×2 km grid in surface soils of Rizhao city, and analyzed sources and risk pattern of 10 heavy metals (As, Cd, Co, Cr, Cu, Hg, Mn, Ni, Pb and Zn). The combination of Multivariate statistics analysis and Geostatistical methods was applied to identify the sources and hazardous risk of heavy metals in soils.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Heavy metals emitted from automobile exhausts and those present in vehicle tires are also deposited in farmland, driven by climatic factors such as rainfall, further affecting the accumulation of Cd and Hg. In line with this, our results are similar to a previous study (Liu et al, 2016;Turkyilmaz et al, 2018), whereby distance from a road was considered one of the most important factors influencing the potential ecological risks of Cd and Hg in farmland soil.…”
Section: Discussionsupporting
confidence: 92%
“…Heavy metals emitted from automobile exhausts and those present in vehicle tires are also deposited in farmland, driven by climatic factors such as rainfall, further affecting the accumulation of Cd and Hg. In line with this, our results are similar to a previous study (Liu et al, 2016;Turkyilmaz et al, 2018), whereby distance from a road was considered one of the most important factors influencing the potential ecological risks of Cd and Hg in farmland soil.…”
Section: Discussionsupporting
confidence: 92%
“…3 and Supplementary Materials Table B. [5][6]. Both the total heterogeneity and the residual, unexplained heterogeneities were significant (Supplementary Materials Table B.5-6).…”
Section: Zn Accumulationmentioning
confidence: 97%
“…3 and Supplementary Materials Table B. [5][6]. The accumulation rate of Zn was significantly different among plant parts, as willow stems ac Fig.…”
Section: Zn Accumulationmentioning
confidence: 98%
See 1 more Smart Citation
“…Another research carried out in this area showed that Cr, Ni, Co, Mn, Cu, and As were mainly came from natural sources. Cd/Hg and Pb/Zn originated from anthropogenic sources in two different groups [57].…”
Section: Te Apportionment In Urban and Industrial Top Soilmentioning
confidence: 99%